Association between Yingyangbao intervention and nutritional and health status among infants and young children in poverty-stricken areas of Hunan province - Hui-xia LI; Shan YUAN; Jian-fei ZHENG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze effects of Yingyangbao (YYB) intervention - a community-based complementary food supplement program on nutritional and health status of infants and young children aged 6 - 23 months in poverty-stricken regions. MethodsA combination of multistage sampling and random isometric sampling was used to recruit 12 619 infants and young children aged 6 - 23 months in 42 poverty-stricken counties of Hunan province. Questionnaire survey, body length and weight measurement, and hemoglobin detection were conducted among the participants between August and October 2020. According to the consumption of YYB, all participants were divided into three groups of non-consumption (n = 3 438), non-effective consumption (n = 3 119) and effective consumption (n = 6 062). The prevalence rate of protein-energy malnutrition, anemia, two-week fever and diarrhea among the three groups were compared. Multivariate logistic regression was used to analyze effects of effective and non-effective consumption of YYB on nutritional and health status of participants. ResultsAmong the participants with non-consumption, non-effective consumption, and effective consumption of YYB, the prevalence rates were 4.5% ,5.4% , and 4.3% for stunting, 3.4%, 3.9%, and 3.0% for underweight, 3.1%, 3.6%, and 2.7% for wasting, 29.6% , 20.8%, and 15.3% for anemia, 14.3% , 14.5% , and 11.5% for having fever in the two weeks, and 12.0% , 12.1%, and 9.2% for having diarrhea in the two weeks, respectively. Multivariate logistic regression analysis showed that among the participants, effective consumption of YYB was a protective factor against anemia (adjusted odds ratio [aOR] = 0.43, 95% confidence interval [95% CI]: 0.39 - 0.48), two-week fever (aOR = 0.79, 95% CI: 0.70 - 0.90), and two-week diarrhea (aOR = 0.75, 95% CI: 0.65 - 0.86); non-effective consumption of YYB also was also a protective factor against anemia (aOR = 0.61, 95% CI = 0.54 - 0.58). There was no significant association of YYB consumption with stunting (aOR = 0.95, 95% CI = 0.77 - 1.17), underweight (aOR = 0.89, 95% CI = 0.70 - 1.13), and wasting (aOR = 0.91, 95% CI = 0.71 - 1.17) among the participants. ConclusionFor the infants and young children in in poverty-stricken regions, effective consumption of Yingyangbao could improve anemia and reduce the two-week prevalence rate of fever and diarrhea; but non-effective consumption of Yingyangbao is less effective than effective consumption in reducing anemia.